A A Method to Quantify Biofilms in Object Glass Using ImageJ - Arief Heru Wicaksono; Rio Risandiansyah; Reza Hakim; Ahmad Akbar Syarieb; Annisa Kurniawati; Iftah Ghina Shafira; Maghfirah Nur Maulani; Hanggia Primadita (CV. AKBAR PUTRA MANDIRI, 2026)
Background: Direct microscopic observation of biofilms is done by observing for the presence of biofilm under a microscope. However, this method is qualitative and not quantitative. Analysis of these biofilm structures using image processing software may provide a method to quantify biofilm production and degradation in glass slides. Objective: To quantify the number and area percentage of microbial structures observable on a slide. This study is an experimental in vitro study. Methods: Biofilm production was done by submerging slides in petri dishes filled with Brain Heart Infusion with 2% sucrose (w/v) and inoculating it with Staphylococcus aureus. The petri dishes were incubated undisturbed for 48 hours at 37°C (n=3).The slides were then submerged in distilled water (Group 1) or detergent (Group 2) for 5 minutes before staining with 0.1% crystal violet and observed under a light microscope at 1000x. Images from five fields of view were collected. ImageJ was then used to count the number of microcolonies, aggregate cells, and single cells or cell clusters, based on size, and their respective area percentage. Welch’s T-Test was performed using JASP version 0.18.3. Results: Direct observation of slides shows that microcolonies and cell clusters to be formed in Group 1, and none or little in Group 2, indicating differences in biofilm formation on Group 1 vs Group 2.Based on ImageJ calculation, control slides had an average percentage area for microcolonies, cell agregates, and single cells or clusters of 39.97 ± 9.99%, 8.96 ± 3.19%, and 1.39 ± 0.33%, respectively. Treatment with detergent significantly reduced percentages of microcolonies to 0.33 ± 0.68%, but increased single cell area to 5.27 ± 0.49%. Conclusion: ImageJ can be a valuable tool to quantify biofilm production in glass slides based on the number and percentage area of microcolonies, cell aggregates, and single cells or cell clusters.